Testosterone Concentrations and Cardiovascular Autonomic Neuropathy in Men with Type 1 Diabetes in the Epidemiology of Diabetes Interventions and Complications Study (EDIC). (1st November 2015) - Kim, Catherine; Pop-Busui, Rodica; Braffett, Barbara; Cleary, Patricia A.; Bebu, Ionut; Wessells, Hunter; Orchard, Trevor; Sarma, Aruna V.
Abstract: Introduction: Previous studies have reported that lower testosterone concentrations are associated with cardiovascular autonomic neuropathy (CAN), a risk factor for cardiovascular events. However, no studies have examined this relationship in men with type 1 diabetes, who are at high risk for CAN. Aim: The aim of this study was to examine the associations between testosterone concentrations and measures of CAN in a large, well-characterized cohort of men with type 1 diabetes. Methods: We conducted an analysis of men in the Diabetes Control and Complications Trial (DCCT), a randomized trial of intensive glucose control, and its observational follow-up the Epidemiology of Diabetes Intervention and Complications (EDIC) Study. Testosterone was measured by liquid chromatography mass spectrometry in stored samples from EDIC follow-up years 10 and 17. Regression models were used to assess the cross-sectional relationships between testosterone and CAN measures. Main Outcome Measures: The main CAN measure from EDIC follow-up year 17 was a standardized composite of R–R variation with paced breathing < 15, or R–R variation 15–20 combined with either a Valsalva ratio ≤ 1.5 or a decrease in diastolic blood pressure > 10 mm Hg upon standing. Continuous R–R variation and Valsalva ratio were secondary outcomes. Results: Lower total and bioavailable testosterone concentrations at follow-up years 10 and 17 were not associated with the presence of CAN at year 17. In analyses using Valsalva ratio as a continuous measure, higher total ( P = 0.01) and bioavailable testosterone concentrations ( P = 0.005) were associated with a higher (more favorable) Valsalva ratio after adjustment for covariates including age, body mass index, smoking status, hypertension, and glycemia. Conclusions: Testosterone levels are not associated with CAN among men with type 1 diabetes. Although testosterone is associated with a higher Valsalva ratio, a more favorable indicator, the clinical significance of this association is not known.